PENGARUHÃÂ LATARÃÂ BELAKANGÃÂ ORANGÃÂ TUAÃÂ SEBAGAIÃÂ GURUÃÂ ÃÂ TERHADAPÃÂ MINATÃÂ MENGAJARÃÂ PADAÃÂ MAHASISWAÃÂ ÃÂ - FajarÃƒÂ‚Ã‚Â K, AndyÃƒÂ‚Ã‚Â ÃƒÂ‚Ã‚Â Rudiyanto; KarsonoÃƒÂ‚Ã‚Â , -; YudionoÃƒÂ‚Ã‚Â , Heri (Jurnal Pendidikan Teknik Mesin, 2008)
PenelitianÃÂ  iniÃÂ mengungkapkanÃÂ permasalahanÃÂ pengaruhÃÂ  latarÃÂ belakangÃÂ orangÃÂ tuaÃÂ sebagaiÃÂ guruÃÂ terhadapÃÂ minatÃÂ mengajarÃÂ padaÃÂ mahasiswaÃÂ ProgramÃÂ StudiÃÂ PendidikanÃÂ TeknikÃÂ MesinÃÂ UniversitasÃÂ NegeriÃÂ SemarangÃÂ angkatanÃÂ 2007ÃÂ  danÃÂ  2008.ÃÂ  BerdasarkanÃÂ  hasilÃÂ  penelitianÃÂ  dapatÃÂ  disimpulkanÃÂ  bahwaÃÂ  latarÃÂ  belakangÃÂ  orangÃÂ  tuaÃÂ  sebagaiÃÂ  guruÃÂ mempengaruhiÃÂ minatÃÂ mengajarÃÂ mahasiswaÃÂ sebesarÃÂ 38,24%.ÃÂ TetapiÃÂ variabelÃÂ latarÃÂ belakangÃÂ orangÃÂ tuaÃÂ sebagaiÃÂ guruÃÂ bukanÃÂ merupakanÃÂ satuÃ¢â¬ÂsatunyaÃÂ faktorÃÂ yangÃÂ mempengaruhiÃÂ minatÃÂ mengajarÃÂ padaÃÂ mahasiswa. KataÃÂ kunciÃÂ :ÃÂ LatarÃÂ BelakangÃÂ OrangÃÂ TuaÃÂ SebagaiÃÂ Guru,ÃÂ MinatÃÂ MengajarÃÂ ThisÃÂ researchÃÂ revealsÃÂ theÃÂ problemÃÂ inÃÂ whichÃÂ theÃÂ parentsÃ¢â¬â¢ÃÂ socialÃÂ backgroundÃÂ asÃÂ teacherÃÂ affectsÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ teaching.ÃÂ TheÃÂ studentsÃÂ wereÃÂ fromÃÂ MechanicalÃÂ EngineeringÃÂ EducationÃÂ programÃÂ SemarangÃÂ StateÃÂ UniversityÃÂ yearÃÂ 2007ÃÂ andÃÂ 2008.ÃÂ AccordingÃÂ toÃÂ theÃÂ resultÃÂ ofÃÂ theÃÂ research,ÃÂ theÃÂ parentsÃ¢â¬â¢ÃÂ socialÃÂ backgroundÃÂ asÃÂ teacherÃÂ affectsÃÂ studentsÃ¢â¬â¢ÃÂ  interestÃÂ  inÃÂ  teachingÃÂ aboutÃÂ 38,24%.ÃÂ However,ÃÂ  thisÃÂ  factorÃÂ  isÃÂ notÃÂ theÃÂ onlyÃÂ factorÃÂ affectingÃÂ studentsÃ¢â¬â¢ÃÂ interestÃÂ inÃÂ teaching.ÃÂ ItÃÂ isÃÂ justÃÂ oneÃÂ ofÃÂ manyÃÂ factors. ÃÂ  Keywords:ÃÂ parentsÃ¢â¬â¢ÃÂ socialÃÂ backgroundÃÂ asÃÂ teacher,ÃÂ teachingÃÂ interest